Regimes of legality / edited by Berti, Daniela - Berti, Daniela (ed.) (New Delhi, 2015)
An anthropological study on judicial practices in South Asia, this volume takes criminal cases as frameworks to examine power dynamics within a legal setting. Case studies in this book analyse a set of state and non-state institutions and the practices of people associated with them. The essays delve into the underlying tension in institutional contexts between legal practitioners such as police officers, lawyers and judges who orient their claims towards neutralism, objectivity and equality and a set of everyday interactions and decisions where cultural, social and political factors play a major role. This volume is based on the premise that the study of judiciary cases, in all their multifaceted complexity, provides a pertinent and original angle from which to access some issues of South Asia. The contributors examine the discourses and relationships around criminal cases that shape how ideas circulate in the public sphere and how mediation and negotiation between different actors characterize police and court practices. Book Features: Provides an anthropological approach Examines the way criminal cases are dealt with by courts in South Asia Takes criminal cases as a framework to study how power dynamics and individual strategies either comply or clash with a legal setting Examines a set of state and non-state institutions and the practices of people associated with them Analyses the underlying tension in institutional contexts Table of Contents: Acknowledgements Foreword by Anthony Good Introduction '3 punishments for 3 mistakes': Negotiating between Courts, Police and Mediation in Family Law and Family Violence ' Pyar Kiya to Darna Kya ': On Criminalizing Love Binding Fictions: Contradicting Facts and Judicial Constraints in a Narcotics Case in Himachal Pradesh The 'Secularism Case': Prosecution of a Hindu Activist before a Quasi-judicial Authority in the Nepal Tarai A Strong Law for the Weak: Dalit Activism in a District Court of Uttar Pradesh Cultures of Policing: Panchayat-Police Practices and the Making of a Criminal Case The Devil's Court!' The Trial of 'Katta Panchayat' in Tamil Nadu From 'She-males' to 'Unix': Transgender Rights and the Productive Paradoxes of Pakistani Policing From a Comparative Perspective: Criminal Cases involving South Asian People at French Assize Courts Index Notes on Editors and Contributors
Keywords: Law